Organoleptic Test of Nutmeg Pulp Residue Tea (Myristica fragrans Houtt) As a Nutriceutical - Chomsa Dintasari Umi Baszary; Dece Elisabeth Sahertian (Pattimura University, 2025)
Nutmeg (Myristica fragrans Houtt) is a native Indonesian spice, and its pulp is often discarded as waste after juice production. However, the residue still contains essential oils and active compounds such as flavonoids, phenols, and myristicin, which may benefit human health. This study aims to evaluate the potential of nutmeg pulp residue as a nutraceutical herbal tea through organoleptic testing, assessing aroma, taste, clarity, and color. The research employed a completely randomized design with three replications. Organoleptic and hedonic tests were carried out on 25 panelists using Friedman and Wilcoxon tests. Results showed that tea clarity scored highest in preference (3.72), followed by aroma (2.28), taste (2.18), and color (1.82). The nutmeg pulp tea was generally acceptable, although improvements in color and flavor intensity are needed. This innovation offers an ecological and economic solution for waste utilization, with potential for rural product diversification and health benefits.